Preoperative Anemia Management: Value-based Care for Orthopedic Surgery. Issue 1 (March 2020) - Heller, Lori B.; Shander, Aryeh
Abstract : Preoperative anemia is common in elective orthopedic surgical patients and is an independent risk factor for perioperative morbidity and mortality. The detrimental effects of anemia on surgical outcomes impact the costs associated with perioperative care as well. In addition to the direct expenditures related to the complications of anemia, perioperative anemia is the leading predictor of perioperative transfusion and it is estimated that up to 6 million dollars are spent on transfusion-related costs per hospital per year. Anemia is a preventable and manageable condition that can often be treated effectively without relying on blood transfusion. In addition to providing optimal outcomes for orthopedic patients, preoperative anemia management is an effective strategy to lower the overall cost of care of surgical patients.